Large-eddy simulation of the flow in a direct injection spark ignition engine using an open-source framework - Dias Ribeiro, Mateus [UNESP]; Mendonça Bimbato, Alex [UNESP]; Araújo Zanardi, Maurício [UNESP]; Perrella Balestieri, José Antônio [UNESP]; Schmidt, David P (SAGE Publications, 2020)
Direct injection spark ignition engines aim at reducing specific fuel consumption and achieving the strict emission standards in state of the art internal combustion engines. This can be achieved by research comprising experimental methods, which are normally expensive and limited, and computational fluid dynamics methods, which are often more affordable and less restricted than their experimental counterpart. In the latter approach, the costs are mainly related to the acquisition, usage, and maintenance of computational resources, and the license cost when commercial computational fluid dynamics codes are used. Therefore, in order to make the research of direct injection spark ignition engines and their internal processes more accessible, this article proposes a novel open-source and free framework based on the OpenFOAM computational fluid dynamics library for the simulation of the internal flow in direct injection spark ignition engines using a large-eddy simulation closure for modeling the turbulence within the gas phase. Finally, this framework is tested by simulating the Darmstadt engine in motored operation, validating the results with experimental data compiled by the Darmstadt Engine Workshop.
Keywords: computational fluid dynamics; direct injection spark ignition; Internal combustion engine; large-eddy simulation; OpenFOAM